Does the use of nest materials in a ground-nesting bird result from a compromise between the risk of egg overheating and camouflage? - Jesús Gómez (Biology Open, 2019)
Many studies addressing the use of nest materials by animals have focused on only one factor to explain its function. However, the consideration of more than one factor could explain the apparently maladaptive choice of nest materials that make nests conspicuous to predators. We experimentally tested whether there is a trade-off in the use of nest materials between the risks of egg predation versus protection from overheating. We studied the ground-nesting Kentish plover, Charadrius alexandrinus, in southern Spain. We added materials differing in thermal properties and coloration to the nests, thus affecting rates of egg heating, nest temperature and camouflage. Before these manipulations, adults selected materials that were lighter than the microhabitat, probably to buffer the risk of egg overheating. However, the adults did not keep the lightest experimental materials, probably because they reduced camouflage, and this could make the nests even more easily detectable to predators. In all nests, adults removed most of the experimental materials independently of their properties, so that egg camouflage returned to the original situation within a week of the experimental treatments. Although the thermal environment may affect the choice of nest materials by plovers, ambient temperatures were not so high at our study site as to determine the acceptance of the lightest experimental materials.